Inhibitors of Antibiotic Efflux by AcrAB-TolC in Enterobacter aerogenes - Lieutaud, A.; Guinoiseau, E.; Lorenzi, V.; Giuliani, M.C.; Lome, V.; Brunel, J-M.; Luciani, A.; Casanova, J.; Pages, J-M.; Berti, L.; Bolla, J-M. (Anti-Infective Agents, 2013)
AcrAB-TolC is involved in the multi-drug resistance (MDR) phenotype of numerous bacterial species. Herein we compared the antibacterial activity of geraniol, a monoterpene found in many plant extracts and derivatives against two isogenic strains of Enterobacter aerogenes, a clinical MDR isolate and its acrAB deletion mutant. These compounds had very different MIC values, which was dependent on the structural features of the compound. Some of the molecules, including geraniol, had a higher MIC for the MDR strain than for the deletion mutant. A similar result was obtained for PAßN, a well-known efflux-pump inhibitor. Conversely, some molecules, including geranylamine, exhibited the same intrinsic activity against both strains, suggesting they are not substrates of AcrAB-TolC. To report efflux activity, we then compared the ability of the compounds to decrease chloramphenicol resistance. Two compounds, geraniol and geranylamine were shown to decrease the MIC for chloramphenicol to the same extent as PAßN. Considering that PAßN is a competitive inhibitor of AcrAB-TolC and that geranylamine is an efficient inhibitor but not a substrate, we suggest that geranylamine inhibits AcrAB-TolC through a non-competitive mechanism. The results are discussed in light of the recent advances in the structural and mechanical features of AcrAB-TolC.
Keywords: Antibiotic-resistance